Respiration, oxidative phosphorylation, and uncoupling protein in Candida albicans - Cavalheiro,R.A. (2004)
The respiration, membrane potential (Dy), and oxidative phosphorylation of mitochondria in situ were determined in spheroplasts obtained from Candida albicans control strain ATCC 90028 by lyticase treatment. Mitochondria in situ were able to phosphorylate externally added ADP (200 µM) in the presence of 0.05% BSA. Mitochondria in situ generated and sustained stable mitochondrial Dy respiring on 5 mM NAD-linked substrates, 5 mM succinate, or 100 µM N,N,N',N'-tetramethyl-p-phenylenediamine dihydrochloride plus 1 mM ascorbate. Rotenone (4 µM) inhibited respiration by 30% and 2 µM antimycin A or myxothiazole and 1 mM cyanide inhibited it by 85%. Cyanide-insensitive respiration was partially blocked by 2 mM benzohydroxamic acid, suggesting the presence of an alternative oxidase. Candida albicans mitochondria in situ presented a carboxyatractyloside-insensitive increase of Dy induced by 5 mM ATP and 0.5% BSA, and Dy decrease induced by 10 µM linoleic acid, both suggesting the existence of an uncoupling protein. The presence of this protein was subsequently confirmed by immunodetection and respiration experiments with isolated mitochondria. In conclusion, Candida albicans ATCC 90028 possesses an alternative electron transfer chain and alternative oxidase, both absent in animal cells. These pathways can be exceptional targets for the design of new chemotherapeutic agents. Blockage of these respiratory pathways together with inhibition of the uncoupling protein (another potential target for drug design) could lead to increased production of reactive oxygen species, dysfunction of Candida mitochondria, and possibly to oxidative cell death.